Juventud en el municipio de Barrancabermeja: problemáticas socioeconómicas y participación (2013)
This paper characterizes the present situation of the youth population of the town of Barrancabermeja and the joint processes of youth organizations during the period 2004-2010. Thus, as young people talk about how their organizations were consolidated and adapted to social changes, it was possible to identify socioeconomic issues associated with poverty and lack of opportunities, and problems related to management capacity affecting youth participation.